Artificial Intelligence Engines and Smart Systems in Developing an Integrated Model for Contemporary Leadership Theories - Sakher Farea Ghaleb Algonaid; Ayoub Qaid Naji Almaidama (International Journal of Technology and Education Research, 2026)
The rapid evolution of Artificial Intelligence (AI) technologies and smart systems has fundamentally reshaped the organizational landscape, creating a knowledge and methodological gap between technological advancement and the current theoretical frameworks of contemporary leadership. This research addresses this gap by investigating how AI engines and smart systems can contribute to the development and crystallization of an integrated model for contemporary leadership theories, particularly within the emerging hybrid work environment. Adopting a Descriptive-Analytical Approach through an in-depth desk review and critical analysis of recent academic literature, the study analyzes the impact of AI on core leadership concepts and identifies the new competencies required for leaders. The analysis reveals that AI significantly enhances dimensions of Transformational Leadership, such as Individualized Consideration and Intellectual Stimulation, but simultaneously challenges the maintenance of Idealized Influence and Inspirational Motivation. The study highlights that the primary challenge in integrating smart systems is not technical, but ethical, necessitating robust governance frameworks. Consequently, the research proposes an Integrated Model: Leadership as a Strategic and Ethical Mediator. This model shifts the leader's role from an administrative supervisor to a mediator who focuses on Formulating the Hybrid Vision, ensuring Ethical Governance of AI decisions, and Enhancing Cognitive Adaptation among employees. The model emphasizes the necessity of new Hybrid Competencies, including Digital Emotional Intelligence and Algorithmic Ethical Thinking, to ensure effective and ethical leadership in the digital age. The findings underscore that Transformational Leadership remains the most effective style for managing digital change, provided it is augmented by these new competencies and the proposed mediator role.